Glomerular Endothelial Vesicles in a Renal Allograft: An Unusual Pattern of Immunoglobulin Deposition in a Patient With Biclonal Gammopathy of Unknown Significance. (June 2015) - Flatley, Ellen M.; Segal, Gerald M.; Batiuk, Thomas D.; Bennett, William M.; Houghton, Donald C.; Troxell, Megan L.
Abstract : Paraproteins have varied effects on the kidney on the basis of molecular structure, concentration, and renal function. Prototypical patterns include myeloma cast nephropathy, monoclonal immunoglobulin deposition disease, and amyloid, among others. We report a 69-year-old man with end-stage diabetic nephropathy and biclonal gammopathy of unknown significance. Serum monoclonal immunoglobulin G (IgG)-κ and urine monoclonal free λ light chains were identified during workup for nephrotic syndrome. A native renal biopsy demonstrated diabetic nephropathy, without indication of paraprotein-related pathology. After transplantation, a surveillance biopsy showed endothelialitis (type 2 rejection) and abundant eosinophilic droplets, nearly occluding glomerular capillary loops. Electron microscopy localized tightly packed electron-dense vesicles in glomerular endothelial cells. Immunofluorescence studies revealed IgG-κ–dominant endothelial staining, along with λ monotypic protein resorption droplets in tubules. Two additional biopsies within the following year showed this same paraprotein distribution, with some increase in mesangial sclerosis. Two years after transplant the patient remains asymptomatic with normal creatinine levels. Literature review yields rare cases of immunoglobulin crystalline deposits in multiple glomerular cell types, rarely including endothelial cells; however, this appears to be the first report of monoclonal immunoglobulin vesicles localized solely to endothelial cells. As these vesicles were not seen in the native kidney biopsy, we hypothesize an interaction of alloimmune-mediated endothelial injury and the physiochemical properties of the IgG-κ paraprotein. In addition, this case illustrates simultaneous different patterns of accumulation of monoclonal immunoglobulin and light chain components in this unique patient with biclonal gammopathy of unknown significance.